Perlindungan Hukum Penggunaan Anime Sebagai Suatu Merek Usaha Ditinjau dari Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Sara Christiany Nggauk; Orpa J. Nubatonis; Chatryen M. Dju Bire (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
The use of anime as a business mark without the permission of the creator or copyright holder of the anime is an infringement of copyright. Copyright infringement of the use of anime as a business mark may be subject to criminal sanctions and/or civil sanctions. The type of research that the author uses is Normative legal research (Library Research) which is carried out by examining library materials (secondary data) or legal materials such as reviewing theories, laws and regulations (law in book) related to this writing through literature studies. The legal consequences of using anime as a business brand without permission can be subject to sanctions which are based on Law Number 28 of 2014 concerning copyright described in Article 9 paragraph (1), Article 112 paragraph (1), Article 113 paragraph (1), also in Law Number 20 of 2016 concerning trademarks and geographical indications which are regulated in Article 100 paragraph (1), (2) and (3).Before using anime as a trademark, business actors must ensure that they have obtained official permission from the copyright holder to avoid the risk of legal sanctions.